ANALISIS DAYA SAING EKONOMI SEKTORAL KABUPATEN OGAN KOMERING ULU SELATAN - Pandriadi, Pandriadi; Ningsih, Endang Kusdiah; Novianty, Dwi Eka; mario, asma (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2021)
This research aims to analize the competitveness of economy sectoral of OKU Selatan District based on secondary data from several local institutions. To determine of competitiveness, this research uses Location Qoutient (LQ) Analysis and Classen Tipology. In conclusion, this research shows that based on LQ Analysis and Classen Typology, there are several sectors which has high competitiveness, such as agricultural and manufacturing industry. On the other side this research also shows the sector which has low competitiveness, such as mining and energy.